NATURAL CONVECTION IN RECTANGULAR CAVITIES WITH DIFFERENT ASPECT RATIOS - Nogueira, R. M.; Martins, M. A.; Ampessan, F. (Revista de Engenharia Térmica, 2011)
Natural convection in closed cavities has been extensively studied in recent decades. This spontaneous method of heat transfer has a wide range of applications in engineering. In the present work, natural convection was numerically analyzed in a rectangular cavity heated on one of the sides and cooled on the opposite side. Temperatures of the heated wall and of the cooled wall were assumed to be constant. The objective of these studies was to determine the effects of the aspect ratio and the Rayleigh number on flow behavior and heat transfer in the cavity. In the simulations, the Rayleigh number drastically influenced the flow profile and heat transfer inside de cavity, as well as the thickness of the thermal boundary layer. It was also verified that the Nusselt number is strongly dependent on the L/D (Length/Height) ratio, and that this dimensionless variable increases with the increase of the W/L. The simulation of natural convection problems in the CFD Studio satisfactorily described the studied situations.